Evaluation of proteasomal gene polymorphisms in Lithuanian patients with asthma - Zemeckiene, Zivile; Sitkauskiene, Brigita; Gasiuniene, Edita; Paramonova, Natalija; Tamasauskiene, Laura; Vitkauskiene, Astra; Sjakste, Tatjana; Sakalauskas, Raimundas (The Journal of asthma, 2015)
Abstract Objective: To investigate polymorphisms of proteasomal genes PSMA6 (rs1048990 and rs2277460), PSMC6 (rs2295826 and rs2295827) and PSMA3 (rs2348071) in Lithuanian patients with asthma. Methods: One-hundred forty-six asthma patients and 150 control subjects were studied. DNA was extracted from peripheral blood samples. Five single nucleotide polymorphisms (SNP's) of the three proteasomal genes were analyzed using allele-specific amplification or the cleaved amplified polymorphic sequence method. Results: While certain alleles and genotypes of PSMA6 rs2277460 and rs1048990 and PSMA3 rs2348071 SNP's occurred more frequently in asthma patients than in controls, no statistically significant differences in alleles or genotypes of PSMA6, PSMC6 or PSMA3 were observed between asthma patients and control subjects. However, when male and female study subjects were considered separately, we found that the CG genotype of PSMA6 rs1048990 is significantly more frequent in male asthma patients compared to male control subjects. Conclusions: We found no significant differences in frequencies of selected five proteasomal gene PSMA6, PSMC6 and PSMA3 SNP's between asthma patients and control subjects overall. Among male subjects, however, the CG PSMA6 rs1048990 genotype was significantly more frequent in asthma patients compared with control subjects.